Prohibitin modulates periodontium differentiation in mice development - Aryal, Yam Prasad; Han, Song-Yi; Rana, Bandana; Neupane, Sanjiv; Kim, Tae-Young; Pokharel, Elina; Ha, Jung-Hong; Jung, Jae-Kwang; An, Chang-Hyeon; Kim, Ji-Youn; Yamamoto, Hitoshi; Lee, Youngkyun; et al. (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Prohibitin (PHB) is an essential scaffold protein that modulates signaling pathways controlling cell survival, metabolism, inflammation, and bone formation. However, its specific role in periodontium development remains less understood. This study aims to elucidate the expression pattern and function of PHB in periodontium development and its involvement in alveolar bone formation. Methods: Immunolocalization of PHB in the periodontium of postnatal (PN) mice were examined. Phb morpholino was micro-injected into the right-side mandible at PN5, corresponding to the position where the alveolar bone process forms in relation to the lower first molar. The micro-injection with a scramble control (PF-127) and the left-side mandibles were used as control groups. Five days post-micro-injection, immunohistochemical analysis and micro-CT evaluation were conducted to assess bone mass and morphological changes. Additionally, expression patterns of signaling molecules were examined following Phb downregulation using 24-h in vitro cultivation of developing dental mesenchyme at E14.5. Results: The immunostaining of PHB showed its localization in the periodontium at PN5, PN8, and PN10. The in vitro cultivation of dental mesenchyme resulted in alterations in Bmps, Runx2, and Wnt signalings after Phb knock-down. At 5 days post-micro-injection, Phb knocking down showed weak immunolocalizations of runt-related transcription factor (RUNX2) and osteocalcin (OCN). However, knocking down Phb led to histological alterations characterized by decreased bone mass and stronger localizations of Ki67 and PERIOSTIN in the periodontium compared 1 to control groups. The micro-CT evaluation showed decreased bone volume and increased PDL space in the Phb knock-down specimens, suggesting its regulatory role in bone formation. Discussion: The region-specific localization of PHB in the margin where alveolar bone forms suggests its involvement in alveolar bone formation and the differentiation of the periodontal ligament. Overall, our findings suggest that Phb plays a modulatory role in alveolar bone formation by harmoniously regulating bone-forming-related signaling molecules during periodontium development.